Chemical Examination of the Fruits of Citrus reticulate Blanco - Saxena, V.K.; Shrivastava, Preeti (Asian Journal of Chemistry, 2010)
The present paper reports the isolation and identification of non-flavonoidic and flavoniodic constituents from the fruits of Citrus reticulata.